Short Communication: The composition of undergrowth vegetation in the Gendol Riverbank, Sleman District, Yogyakarta, Indonesia - Atus Syahbudin; ALNUS MEINATA; WIYONO; RIDLA ARIFRIANA (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Syahbudin A, Meinata A, Arifriana R, Wiyono. 2020. The composition of undergrowth vegetation in the Gendol Riverbank, Sleman District, Yogyakarta, Indonesia. Biodiversitas 21: 1786-1792. Gendol river is one of the rivers affected by a pyroclastic blast from Mount Merapi eruption in 2010. This river flows through several villages, such as Glagaharjo, Kepuharjo, Wukirsari, and Argomulyo. On this riverbank, vegetation has grown naturally post-eruption of Mount Merapi and is continues to change. Some vegetation was also planted by the community. This study aims to find out the composition of the undergrowth vegetation on the Gendol riverbank in Cangkringan Sub-district. The data was obtained systematically by marking 10 sample plots of 5 m x 5 m and 2 m x 2 m size, on each side of the bank. A total of 68 species were recorded in this study which consisted of 29 trees species in seedlings and saplings stage, 34 species of herbs and shrubs, and 6 species of grasses. The dominant among the non-tree species are Chromolaena odorata (L.) R.M.King & H.Rob. with an IVI of 43.78%, Alternanthera brasiliana (L.) Kuntze with IVI of 16.6% and Asystasia gangetica (L.) T. Anderson with IVI of 15.78%. Saplings are dominated by Falcataria moluccana (Miq.) Barneby & J.W. Grimes with IVI of 32.81%, followed by Leucaena leucocephala (Lam.) De Wit (IVI-24.41%) and Melia azedarach (IVI-14.28%).